Advances in additive manufacturing of metal-based functionally graded materials. (2nd January 2021) - Reichardt, Ashley; Shapiro, Andrew A.; Otis, Richard; Dillon, R. Peter; Borgonia, John Paul; McEnerney, Bryan W.; Hosemann, Peter; Beese, Allison M.
ABSTRACT: Over the 2010s technological improvements allowed metal additive manufacturing to graduate from a prototyping tool to a widespread, full-scale manufacturing process. Among the capabilities still under development, however, is the ability to locally tailor alloy composition and properties to fabricate bulk, complex geometry functionally graded materials (FGMs), eliminating the need for dissimilar-metal welds and joints. The challenge of compositional grading involves overcoming chemical, metallurgical, and thermal property differences to achieve a continuous structure between a wide range of selected combinations of alloys. In this review, examples are discussed of fabricating FGMs joining a variety of combinations of stainless, nickel, titanium and copper alloys, and FGMs joining metals to ceramics and metal-matrix composites. The change in design strategy enabled by practical FGMs may lead to effective use of biomimetic designs that are both much more efficient as well as aesthetically pleasing.